Perancangan Sistem Aplikasi Tracking Pendukung Touring Secara Real Time Menggunakan Firebase Berbasis Android (Studi Kasus Komunitas Motor Trigramyama Salatiga) - Tri Mulyono; Pratyaksa Ocsa Nugraha Saian (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Trigramyama is a motorbike community that often holds touring activities outside the city with quite some members. With the large number of members participating, there are also many problems encountered when doing the touring, one of the problem is coordination between members when there are members who are separated from the group. This research will be designed a tracking system Android-based application in the Trigramyama motorbike community using firebase technology that utilizes the real-time database feature, besides this design uses GPS technology taken from the Google Maps API. this touring supporting tracking application allows all users to know the whereabouts of other members and also makes it easier to coordinate. The level of satisfaction from using this application reaches 85%, from the results of the presentations it can be concluded that this application is following the needs of the Trigramyama motorcycle community.